Montgomery family papers - Montgomery, Emily Redington, 1839-1898.; Montgomery, George Redington, 1870-1945.; Montgomery, Giles Foster, 1835-1888.; Montgomery, Marshall Hugh, 1909-2000.
Correspondence, speeches, writings, financial records, newspaper clippings, and other papers of members of the Montgomery family and allied Peck and Perkins families.
Includes papers of Giles Foster Montgomery and Emily Redington Montgomery relating to their years as missionaries in Turkey (1863-1888); papers of their son, George Redington Montgomery; and correspondence of their daughter, Mary Borglum, and her husband, Gutzon Borglum. Papers of George Redington Montgomery document his academic and ministerial career and his work with the Paris Peace Conference, Inter-allied Commission on Mandates in Turkey (King-Crane Commission), and the Armenia America Society; and papers of his son, Marshall Hugh Montgomery, concern his career with Aubrey G. Langston & Co. as a New York securities dealer and banker. George Redington Montgomery's correspondents include Homer S. Cummings, Ernest Gallaudet Draper, John L. Franklin, Robert Lansing, Henry Cabot Lodge, Eugene Meyer, and J.A. Trowbridge, Jr.
Peck family papers consist primarily of correspondence between Frank Henry Peck and family members relating to his experiences in the Civil War with the 12th Connecticut Infantry Regiment, U.S. Army. Subjects include the bombardment of Fort Jackson, La., and Fort Saint Philip, La., and finally, the capitulation and military occupation of New Orleans, La.
Papers of the Perkins family consist chiefly of the correspondence of Newton William Perkins concerning his service with the 13th Connecticut Infantry Regiment, U.S. Army, on board various ships and from different camps, tracing the movement of his regiment from Connecticut to New Orleans and later to Washington, D.C., and Virginia.
Library of Congress Prints and Photographs Division.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Borglum, Gutzon, -- 1867-1941 -- Correspondence; Borglum, Mary -- Correspondence; Cummings, Homer S. -- 1870-1956 -- Correspondence; Draper, Ernest Gallaudet, -- 1885-1954 -- Correspondence; Franklin, John L. -- 1856-1901 -- Correspondence; Lansing, Robert, -- 1864-1928 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Meyer, Eugene, -- 1875-1959 -- Correspondence; Peck, Frank Henry, -- 1836-1864 -- Correspondence; Perkins, Newton William, -- 1839-1902 -- Correspondence; Trowbridge, J. A. -- Jr. -- Correspondence; Montgomery family; Peck family; Perkins family; United States. -- Army -- Military life; United States. -- Army. -- Connecticut Infantry Regiment, 12th (1861-1865); United States. -- Army. -- Connecticut Infantry Regiment, 13th (1862-1866); Aubrey G. Langston & Co; Armenia America Society; Inter-allied Commission on Mandates in Turkey. -- American Section; Banks and banking -- New York (State) -- New York; Missions -- Turkey; Securities -- New York (State) -- New York; Connecticut -- History -- Civil War, 1861-1865.; Fort Jackson (La.) -- History -- Siege, 1862.; Fort Saint Philip (La.) -- History; Louisiana -- History -- Civil War, 1861-1865.; New Orleans (La.) -- History -- Capture, 1862.; New Orleans (La.) -- History -- Civil War, 1861-1865.; Turkey -- Social conditions; United States -- History -- Civil War, 1861-1865 -- Campaigns; Virginia -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.